2018
DOI: 10.1002/per.2139
|View full text |Cite
|
Sign up to set email alerts
|

Social Value Orientation, Expectations, and Cooperation in Social Dilemmas: A Meta–Analysis

Abstract: Interdependent situations are pervasive in human life. In these situations, it is essential to form expectations about the others' behaviour to adapt one's own behaviour to increase mutual outcomes and avoid exploitation. Social value orientation, which describes the dispositional weights individuals attach to their own and to another person's outcome, predicts these expectations of cooperation in social dilemmas—an interdependent situation involving a conflict of interests. Yet, scientific evidence is inconcl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
165
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(182 citation statements)
references
References 139 publications
(202 reference statements)
9
165
1
7
Order By: Relevance
“…While we observed a high initial willingness to cooperate, participants significantly cooperated less after the agent's noncooperative behavior in the second round of the game supporting our hypothesis. These findings are in line with prior research [9], demonstrating that persons are more cooperative when they expect their counterparts to cooperate as well. Thus, after the agent destroyed the participants' trust by being not cooperative, participants did not expect the agent to be cooperative anymore and therefore their own willingness to cooperate also decreases.…”
Section: Discussion Limitations and Future Worksupporting
confidence: 92%
See 1 more Smart Citation
“…While we observed a high initial willingness to cooperate, participants significantly cooperated less after the agent's noncooperative behavior in the second round of the game supporting our hypothesis. These findings are in line with prior research [9], demonstrating that persons are more cooperative when they expect their counterparts to cooperate as well. Thus, after the agent destroyed the participants' trust by being not cooperative, participants did not expect the agent to be cooperative anymore and therefore their own willingness to cooperate also decreases.…”
Section: Discussion Limitations and Future Worksupporting
confidence: 92%
“…Besides the nonverbal behavior of interlocutors, their actual decision-making behavior in the Prisoner's Dilemma is of course also a crucial indicator for trust and cooperation. Pletzer and colleagues [9] found that people are more willing to cooperate when they expect their counterpart to cooperate. Hence, once the trust between the interlocutors has been destroyed by not being cooperative, the perceived cooperativeness of the counterpart will also decrease.…”
Section: Introductionmentioning
confidence: 99%
“…As described above, we also collected data on the two variables expectation and human player, which we explored in a regression models with the other predictors. In line with previous research (Pletzer et al, 2018), expectation turned out to be a significant predictor, b = 0.027, t(155) = -1.104, p < .001., but human player was, as well, b = -0.082, t(155) = -2.094, p = .038. The latter showed a negative slope coefficient, indicating that the less participants believed that the other player was human, the more they behaved prosocially afterwards.…”
Section: Resultssupporting
confidence: 90%
“…It has been demonstrated that the more prosocially oriented people are, the more time they spend on others' requests (McClintock & Allison, 1989), the more they donate money for charity (Van Lange et al, 2007), the more socially mindful they select preferable objects (Van Doesum, Van Lange, & Van Lange, 2013), the more often they interpret situations as a cooperative endeavor (Yamagishi et al, 2013), and the more they value moral behavior, including fairness, honesty and equality (Liebrand, Jansen, Rijken, & Suhre, 1986;Sattler & Kerr, 1991;Joireman et al, 2003). Prosocials and proselfs differ in their world views resulting in different expectations of others' behavior (see also generalized expectations in Pletzer et al, 2018;Bogaert, Boone & Declerck, 2008;Van Lange, 1992;Kelley & Stahelsky, 1970): Proselfs think that others would act in a selfish way when given the option to cooperate, whereas prosocials have a stronger initial expectation that others will cooperate in such situations.…”
mentioning
confidence: 99%
“…Las investigaciones centradas en el estudio de valores prosociales, desde diferentes perspectivas, han sido un tema de gran interés desde la década del setenta (Brownell & Carriger, 1990;Correa-Chávez, 2016;Kagan & Madsen, 1971;Matusov, Bell & Rogoff, 2002). Numerosas investigaciones se han centrado en la orientación del valor social (Social Value Orientationsvo), la cual intenta establecer las diferencias individuales entre sujetos cooperativos e individualistas con el uso de diferentes medidas asociadas (Pletzer, Balliet, Joireman, Kuhlman, Voelpel & Van Lange, 2018). La mayoría de estudios reportados intentan describir qué tanto un individuo o sociedad es individualista, cooperativa o competitiva (Pletzer et al 2018).…”
Section: Introductionunclassified